2022
DOI: 10.21203/rs.3.rs-1408525/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deepfakes and Scientific Knowledge Dissemination

Abstract: Science misinformation on topics ranging from climate change to vaccines have significant public policy repercussions. Artificial intelligence-based methods of altering videos and photos (deepfakes) lower the barriers to the mass creation and dissemination of realistic, manipulated digital content. The risk of exposure to deepfakes among education stakeholders has increased as learners and educators rely on videos to obtain and share information. We detail the results of the first study to understand the vulne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In addition, Graso et al (2022) found that individuals with high trust in the science of COVID-19 believed that even unsupported claims about COVID-19 would be supported by scientific evidence. Such findings are also in line with recent studies by Xiao et al (2021) and Doss et al (2023), who found that individuals with high trust in specific information sources (e.g. social media) are more vulnerable to being manipulated by these sources (e.g.…”
Section: Background and Hypothesessupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, Graso et al (2022) found that individuals with high trust in the science of COVID-19 believed that even unsupported claims about COVID-19 would be supported by scientific evidence. Such findings are also in line with recent studies by Xiao et al (2021) and Doss et al (2023), who found that individuals with high trust in specific information sources (e.g. social media) are more vulnerable to being manipulated by these sources (e.g.…”
Section: Background and Hypothesessupporting
confidence: 92%
“…social media) are more vulnerable to being manipulated by these sources (e.g. by deepfake videos; Doss et al, 2023).…”
Section: Background and Hypothesesmentioning
confidence: 99%